Evaluation of Liquefaction Potential in the Budong-Budong Dam Foundation Plan to Prevent Dam Failure Due to Liquefaction Using a Deterministic Approach - Erista, Dicky; Sukamta, Sukamta (TEKNIK, 2025)
The Budong-Budong Dam, located in the district of Central Mamuju, West Sulawesi Province, is currently under construction. The foundation plan of the dam is a layer of river deposits (alluvial) with a thickness of 25 m and a shallow water table depth, which has been shown to have liquefaction potential. This study aims to assess the liquefaction potential of the river deposit layer using some additional SPT test data. This research is expected to confirm the liquefaction potential of the river deposits layer so that it can be considered by the dam owner in determining the foundation excavation limit and prevent dam failure due to liquefaction. The liquefaction potential analysis was carried out using a semi-empirical procedure according to Idriss and Boulanger (2006). The analysis was performed under 2 (two) earthquake conditions, namely Operating Basis Earthquake (OBE) and Safety Evaluation Earthquake (SEE), using different values of fines content (5%, 15%, 35%) and earthquake magnitudes (6.8, 7.0, 7.3, 7.5 and 7.7). The analysis shows that the foundation plan of the Budong-Budong Dam has the potential for liquefaction under both OBE and SEE conditions, which generally occurs at a depth of about 10-12 m from the ground surface. The liquefaction potential of finer-grained river deposits tends to be lower